Identity Dilemma and Post-Colonialism in Conrad's Heart of Darkness - Nazan Eriş (Engiscience Publisher, 2023)
This study aims to examine Conrad's novella "Heart of Darkness" in terms of two diverse themes; identity dilemma and post-colonialism. This narrative follows the protagonist Marlow as he travels to the Congo River and discovers the harsh realities of colonization and its effects on the native people. However, apart from postcolonialism, this study also aims to shed light on how the novella represents the complicated and sometimes contradictory nature of identity via an investigation of the experiences and actions of the characters. At the same time, it is possible to realize that the novella includes a theme of identity dilemma, which can be examined in terms of the Hegelian master-slave dialectic. It represents the nature of oppression, subjugation, and resistance at some point.